Assessing Attitudes of Primary School Teachers towards Free Primary Education in Swaziland: The Case of Shiselweni Region - Mushoriwa, T.D.; Mlangeni, V.T.; Kurebwa, M. (Universitas Pendidikan Indonesia, 2016)
ABSTRACT: This study was designed to assess the attitudes of Primary School teachers towards FPE (Free Primary Education) recently introduced in Swaziland, with the ultimate aim of establishing how the teachers feel about the change given the increase in enrolments in the schools. The survey research design was employed. Data were sourced from 118 teachers (females = 50%) through a semi-structured questionnaire and follow-up interviews. While data were largely analysed through the Likert scale analysis procedures described in this study, Cramerâ€™s V was the statistic used to test if gender significantly influenced attitudes towards FPE. The study found that the majority of the teachers (73%) had negative attitudes towards FPE mainly because of, among other things, large teacher-pupil ratios (1:70) which increased their workload; shortage of resources and infrastructure; being viewed as lowering educational standards; and the fact that the teachers were not consulted despite being the key implementers. Cramerâ€™s V yielded an insignificant positive relationship (0.06) between gender and attitudes; and this meant that gender did not significantly influence the teachersâ€™ attitudes towards the introduction of FPE. KEY WORD: Assessing; Teacher Attitudes; Free Primary Education; Increased Enrolments; Gender.Â ABSTRAKSI: â€œMenilai Sikap Guru-guru Sekolah Dasar terhadap Pendidikan Dasar Gratis di Swaziland: Kasus Daerah Shiselweniâ€. Penelitian dirancang untuk menilai sikap guru-guru Sekolah Dasar terhadap PDG (Pendidikan Dasar Gratis) yang baru-baru ini diperkenalkan di Swaziland, dengan tujuan akhir menentukan bagaimana perasaan para guru tentang perubahan tersebut mengingat meningkatnya pendaftaran murid di sekolah. Desain penelitian survei digunakan dalam penelitian ini. Data bersumber dari 118 guru (perempuan = 50%) yang diperoleh melalui kuesioner semi-terstruktur dan wawancara lanjutan. Data sebagian besar dianalisis melalui prosedur skala Likert, sedangkan V Cramer adalah statistik yang digunakan untuk menguji apakah jenis kelamin secara signifikan mempengaruhi sikap. Studi ini menemukan sebagian besar guru (73%) memiliki sikap negatif terhadap PDG terutama karena, antara lain, besarnya rasio guru-murid (1:70) yang meningkatkan beban kerja; kurangnya sumber daya dan infrastruktur; dipandang akan menurunkan standar pendidikan; dan fakta bahwa guru tidak diajak urun-rembug meskipun sebagai pelaksana kunci. V Cramer menghasilkan hubungan positif yang tidak signifikan (0.06) antara gender dan sikap; dan ini berarti bahwa gender tidak berpengaruh secara signifikan terhadap sikap guru. KATA KUNCI: Menilai; Sikap Guru; Pendidikan Dasar Gratis; Peningkatan Pendaftaran; Gender.Â Â About the Authors: T.D. Mushoriwa, Ph.D. is a Full Professor at the University of Fort Hare in South Africa; V.T. Mlangeni is a Teacher at the Nhlangano Central High School in Swaziland; and M. Kurebwa is a Lecturer at the Zimbabwe Open University, Midlands, in Zimbabwe. Corresponding author is: tmushoriwa@ufh.ac.zaHow to cite this article? Mushoriwa, T.D., V.T. Mlangeni M. Kurebwa. (2016). â€œAssessing Attitudes of Primary School Teachers towards Free Primary Education in Swaziland: The Case of Shiselweni Regionâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Vol.1(2) September, pp.143-150. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Chronicle of the article: Accepted (July 16, 2016); Revised (August 17, 2016); and Published (September 30, 2016).